2018
DOI: 10.4274/tjcd.04834
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Seton Placement in Treatment of Complex Anal Fistula: Analysis of 44 Patients

Abstract: Amaç: Kompleks anal fistül tedavisinde konsensüs bulunmamaktadır. Çeşitli yöntemler bulunmakla birlikte tedavide sıklıkla seton uygulmaları yer alır. Setonlar sıkı ve gevşek olarak konabilir. Gevşek setonlar genellikle uzun süreli drenaj gereken vakarda tercih edilir. Sıkı setonlar ise ağrılı sıkma seansları ve kontinans üzerine olumsuz etkileri nedeniyle hasta konforunu düşürmektedir. Bu çalışmada, kompleks anal fistül tedavisinde sıkı seton alternatif olarak elastik seton uygulaması sonuçlarımızı paylaşmayı … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…37 Seton application in a similar fashion has been reported in the literature but gas and stool incontinence was not monitored in any patient. 38 Similarly, in the study by Vrzgula et al, a loose seton was used in 14 out of 99 patients who were operated on for anal abscesses. In this study, no relapses were observed, and no solid or liquid stool leakage was reported in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…37 Seton application in a similar fashion has been reported in the literature but gas and stool incontinence was not monitored in any patient. 38 Similarly, in the study by Vrzgula et al, a loose seton was used in 14 out of 99 patients who were operated on for anal abscesses. In this study, no relapses were observed, and no solid or liquid stool leakage was reported in any patient.…”
Section: Discussionmentioning
confidence: 99%